2021
DOI: 10.21037/tp-20-392
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative study of one-stage and the novel two-stage urethroplasty using the transected urethral plate and transverse preputial island flap (TPIF) for severe hypospadias: a single-center experience

Abstract: Background: To evaluate a novel two-stage method of urethroplasty using a transected urethral plate and transverse preputial island flap (TPIF) for proximal hypospadias with severe chordee.Methods: We retrospectively analyzed 91 cases of proximal hypospadias, who had undergone either onestage or two-stage urethroplasty. Comparisons between the two groups were made based on age, glans diameter, the length of the urethral defect, and the rate of complications.Results: There was no significant difference in age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In this study, urethrocutaneous stula occurred in 35 patients (35/126, 27.6%) in single-stage group but no patient in two-stage group. A prospective study of Zhu et al [23]. reported that the incidence of urethrocutaneous stula in single-stage TPIFU was 27.3% (18/66) higher than 4.5% (2/44) underwent two-stage TPIFU.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, urethrocutaneous stula occurred in 35 patients (35/126, 27.6%) in single-stage group but no patient in two-stage group. A prospective study of Zhu et al [23]. reported that the incidence of urethrocutaneous stula in single-stage TPIFU was 27.3% (18/66) higher than 4.5% (2/44) underwent two-stage TPIFU.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with the two-stage TPIFU, single-stage procedures may reduce the cost of medical treatment and the anxiety of patients and their families, but single-stage TPIFU led to a higher incidence of postoperative complications than two-stage TPIFU [22,23]. Two-stage TPIFU takes advantage of completing part of the urethra creation in rst stage, and left stula resulting in less stimulation and better healing of distal neourethra.…”
Section: Discussionmentioning
confidence: 99%
“…There were no new techniques described, but modifications were mentioned by different authors in hope of an improved outcome and reducing the complication rate (7)(8)(9). The majority of studies concluded that two-stage surgery leads to improved results compared with one stage (9)(10)(11)(12). The options described are modified Koyanagi technique (13)(14)(15), transverse preputial island flap urethroplasty (10,12,16), inlay (17-19), or buccal mucosa graft (20,21).…”
Section: Surgical Techniques Represents the Most Important Chaptermentioning
confidence: 99%
“…The majority of studies concluded that two-stage surgery leads to improved results compared with one stage (9)(10)(11)(12). The options described are modified Koyanagi technique (13)(14)(15), transverse preputial island flap urethroplasty (10,12,16), inlay (17-19), or buccal mucosa graft (20,21). Tunica vaginalis represents a good coverage material (22-24).…”
Section: Surgical Techniques Represents the Most Important Chaptermentioning
confidence: 99%
“…Pediatric hypospadias is a frequent congenital urinary system abnormality (1) . Approximately one in every 100-300 live male infants is reported to have proximal hypospadias, which is found in 20% of instances.…”
Section: Introductionmentioning
confidence: 99%